Effect of building height on dynamic inelastic response of coupled walls. - Chaker, Driss. (University of Ottawa (Canada), 1990)
Coupled wall structures when subjected to earthquakes possess both strength and deformation capacity beyond the elastic range. Although coupled wall systems have a long history of satisfactory use in stiffening multistory buildings, there is a need for information on the behavior of such structures under strong earthquake motions. Inelastic dynamic analysis was carried out in this research project to develop charts that show variation in ductility requirement with structure height when other structural and ground motion parameters are kept constant. Three structures with different building height, and the same overall geometry were selected for analysis. A total of 20 coupled wall structures were analyzed in this investigation. Each structure was analyzed with different levels of yield strength and two different levels of beam-to-wall strength ratio. The objective of the current study is to establish a relationship between height, strength and ductility requirement. An effort was made to express maximum wall and beam ductility requirement analytically for the coupled wall structures considered in this investigation.
Keywords: Engineering, Civil.